The Transformation of Augmented Reality in Digital Marketing for SMEs in the Furniture Industry (Jurnal Ekonomi Pembangunan Widya Mandira, 2026)
The strategic role of Augmented Reality (AR) in digital marketing and to identify the determining factors that influence the adoption of this technology among Small and Medium Enterprises (SMEs) in the furniture sector. The method used is a literature review involving an examination of various academic journals and credible scientific articles sourced from various digital publication portals. The findings reveal that the use of AR has a positive impact on perceived product fit, customer interaction duration, and consumer purchase intent by reducing the risks associated with online shopping. However, the adoption rate of AR among SMEs remains relatively low due to structural barriers. These barriers include the high cost of creating 3D models, limited digital literacy among the workforce, and suboptimal integration of internal company management systems. In conclusion, the significant potential of AR in the digital marketing transformation of furniture SMEs needs to be supported by a strategic shift toward utilizing more affordable Software as a Service (SaaS)-based AR platforms to address infrastructure and cost limitations.
Keywords: Digital Marketing; Furniture MSMEs; Technology Adoption; Digital Transformation; Consumer Behavior.